Sustainability evaluation of a steel production system in China based on emergy. (20th January 2016) - Pan, Hengyu; Zhang, Xiaohong; Wu, Jun; Zhang, Yanzong; Lin, Lili; Yang, Gang; Deng, Shihuai; Li, Li; Yu, Xiaoyu; Qi, Hui; Peng, Hong
Abstract: The huge energy consumption and high pollutants emission have restrained the sustainable development of China's iron and steel industry. It is very necessary to explore those underlying obstacles which hinder the sustainable development of this industry from a systematic point. This paper adopted an improved emergy based method and a set of indicator system to evaluate the sustainability of steel production enterprises, in which dilution method, disability adjusted life years (DALY) method and potentially disappeared fraction (PDF) method were integrated into classic emergy analysis to quantify the impact of emissions, and then the related indicator system characterizing the industrial production process was put forward. One steel production enterprise in Sichuan Province, China, as a case, was studied using the proposed methods and indicator system. The research results show that this enterprise is not sustainable in the long term, due to large share of nonrenewable inputs and strong dependence on imported inputs; emissions' impact further aggravates this situation due to the increasing environmental loading; the proposed methods and indicator system can act as one of helpful tools for decision-making in steel & iron industry. Finally, this paper gives some corresponding suggestions so as to improve the comprehensive performance of this enterprise. Highlights: The sustainability of a steel production enterprise in China was explored based on improved emergy methods. High share of purchased inputs weakens its economic benefit. Large share of nonrenewable inputs and emissions' impacts lead to its high environmental loading. It has very low level of sustainable development. It is urgent to promote technology reform, energy conservation, pollution control, and marketization reform.